Political Behavior of Beginner Voters in Mayor Election Batam 2015 at Sagulung Kota - Lestari, Linayati; Trysa Lumbantobing, Immanuel; Johar, Siti Sarawati (Journal of Techno-Social, 2018)
One contestant of voters at the election of mayor and vice mayor of Batam in 2015 is a beginner voter Sagulung Sub-district with a significant number compared to other districts in Batam City with the highest number of 199 people. Beginner voters as a political person in preparing the Riau Islands regional government occupies a sizeable portion of any political agenda, the importance of early voters is even used as a booster for the political party voting on the grounds that the novice voters are judged to have minimal information about the candidates. Whereas they claim to be enthusiastic with the regional head electoral system simultaneously but declare that they do not know the candidates, vision and mission and work programs of each candidate, and do not know the procedures in voting and cannot be sure that the portion of the registered voters is interested in claiming to be interested in Certain candidate pairs on the grounds of young leaders and reformers in the election of regional heads and have hope that elected candidates are able to produce policies that favor young people, for example by establishing quality educational facilities and infrastructure in Batam. The purpose of this research is to know political voter behavior in the batam local election period 2015 and the factors that influence it. The method used in this research is descriptive qualitative method, with snowball sampling technique with the acquisition of 67 informants. Beginner voters of the Sagulung Kota Urban Villages are irrational where sociological factors are the dominant factor for them in determining the right to vote should they be rational as they are in the culture of critical young people, but the dominance of the family and the opinion of the majority of the local people's choices affect their political choices. This research has corroborated Dennis Kavanagh's theory with sociological approach, social psychology, and rational choice that influenced the behavior of novice voters in the election of mayor and vice mayor of Batam in 2015.Â Â